Analisis Deskriptif Kesehatan Keluarga pada Masyarakat Desa Pulau Jambu Kecamatan Kampar - Anugrah Anugrah; Yoga Saputra; Meisa Aprianti; M. Raafi Fadhilah; Andika Dalesta (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2026)
Family health is a fundamental component of public health development, as the family represents the smallest social unit shaping individual health behaviors. This study aimed to analyze the family health conditions of the community in Pulau Jambu Village, Kampar District, based on demographic, behavioral, socioeconomic, and environmental factors. A descriptive quantitative approach was employed with a total sample of 153 respondents selected using random sampling, ensuring equal probability for each population member to be included.The results indicated that most respondents were in the productive age group of 19–60 years (68.8%), with farming as the dominant occupation (47.1%). The majority relied on borehole wells as their water source (61.4%); however, 47.1% had septic tank distances ≤10 meters, posing potential risks of water contamination. Regular physical activity was reported by 60.8% of respondents, yet the prevalence of smoking was very high (78.4%). Most respondents had a junior high school education (45.1%), influencing health literacy levels, although 58.2% demonstrated good knowledge of clean and healthy living behavior (PHBS). Health service utilization was relatively high (86.3%), though some residents still practiced traditional treatment.In conclusion, family health conditions are influenced by a combination of behavioral, environmental sanitation, and socioeconomic factors. Strengthening family-based health interventions through PHBS education, smoking control, and environmental sanitation improvement is essential to enhance sustainable community health status.